SISTEM APLIKASI TAGIHAN AIR PADA PERUMAHAN PESONA SERPONG - Muhammad Taufiq Raihan; Martinus Lawolo; Muhammad Bagas R (Journal of Research and Publication Innovation, 2024)
Practical Work (KP) is a concrete manifestation of our commitment as students to provide a positive impact on the surrounding community. In order to meet the needs and demands of the times, this KP program will focus on introducing a water billing application system. Technology has become an important part in various aspects of life, including the management of utilities such as clean water. In many housing developments, water bill management is still done manually, which often causes problems such as recording errors, late payments, and difficulty accessing billing information. Practical Work Program (KP) with the title